Growth and Yield Response of Sweet Corn (Zea mays var. Saccharata Sturt.) at Various Doses of Ammonium Sulfate Fertilizer - Mulyana, Erik; Rosyad, Astryani; Hapsari, Dhika Prita (WBS Laboratory, 2025)
Sweet corn is a horticultural commodity that is widely cultivated and consumed in Indonesia. This study aimed to determine the growth and yield response of sweet corn plants to the application of various doses of ammonium sulfate fertilizer. The research was conducted at Pasir Kuda Experimental Field, Bogor, West Java. This experiment used a randomized complete block design (RCBD)with a single factor, namely the dose of fertilizer application. Treatments were arranged in 4 levels of application, namely: (1) control, (2) standard NPK fertilization, (3) 0.5 dose of N, (4) 1,0 doses of N, (5) 1,5 doses of N, and (6) 2,0 doses of N. The results of this test indicate that the application level of ammonium sulfate fertilizers at the application level of 1,0 doses N fertilizer treatment can generally provide plant height, stem diameter, number of leaves, stover weight, cob weight with husk, cob weight without husk, production plot-1, and productivity which are statistically higher than the control treatment. The application of 1,0 doses N fertilizer treatment had Relative Agronomic Effectiveness (RAE) values that meet the requirements to pass the fertilizer effectiveness test, with the highest RAE value obtained in the application of 1,0 doses N fertilizer at 188%.